1999
DOI: 10.1093/chromsci/37.9.330
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Speciation in Humans and Food Products: A Review

Abstract: Although acute intoxication has become rare, arsenic (As) is still a dangerous pollution agent for industrial workers and people living in the vicinity of emission sources. In humans, only inorganic As is toxic; organic forms present in large amounts in the environment are nontoxic. It is therefore important to be able to differentiate one group from the other using appropriate speciation methods. The authors review the present knowledge of the distribution of As in humans and food products. The three steps of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 81 publications
2
56
0
2
Order By: Relevance
“…6,7) Previous studies on arsenic in seaweed have shown that the majority of arsenic can easily be extracted by water or water/methanol extraction. 34) Our values of the total-As obtained by water extraction using ultrasonication are consistent with the values already reported. 8,9,15,31) The present study indicates that AsSugs in hijiki account for 3.7-27.6% of total-As (Table 4).…”
Section: Discussionsupporting
confidence: 92%
“…6,7) Previous studies on arsenic in seaweed have shown that the majority of arsenic can easily be extracted by water or water/methanol extraction. 34) Our values of the total-As obtained by water extraction using ultrasonication are consistent with the values already reported. 8,9,15,31) The present study indicates that AsSugs in hijiki account for 3.7-27.6% of total-As (Table 4).…”
Section: Discussionsupporting
confidence: 92%
“…4,5 The toxicity of arsenic, as well as its environmental cycling, is heavily dependent on the chemical species, and the development of methods for speciation analysis has been a key component in arsenic studies. 6,7 In spring 2003, severe arsenic contamination of groundwater was uncovered in Kamisu-town, Ibaraki Prefecture, Japan. Several residents using the same well water fell ill with characteristic nervous symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…The concentrations of several trace elements vary considerably even in foods belonging to similar groups belonging to different groups. The problem of trace element analysis can be overcome by freeze-drying of mixed diets as this may lead to six fold enrichment of the component (Benramdane, 1999;Aceto, 2002).…”
Section: Elemental Profilingmentioning
confidence: 99%
“…Pharmaceutical industries (metals in wine (Aceto, 2002), arsenic in food (Benramdane, 1999), and trace elements bound to proteins Biological samples (Ma, 2004). Precious metal estimation at low level, Heavy metal estimation at sub ppm level Rock, Soil, Fly ash (Complete analysis), Environmental sample analysis (Water, Air, Soil, sediments, etc.)…”
Section: Applicationsmentioning
confidence: 99%